Preferences of Students with Visual Impairment between Braille and Screen Reader’s Software - Faiza Jaleel; Faisal Anis (JIE, 2018)
Innovations in technology put great emphasis on the use of technology and provide the variety of learning medium to students with visual impairment, such as screen reader software and braille as learning medium. The purpose of this study was to explore the preferences of students with visual impairment about their learning medium i.e. braille and screen reader’s software. The major question of the study was, what is the difference between braille and screen reader’s software preferences of students with visual impairment? It was a descriptive study. The population of this study consisted of students with visual impairment who experience braille and screen reader software as learning medium. The purposive sampling technique was used to select a sample of 70 students. A five-point rating scale was developed that was consisted on 20 questions. These questions were validated by expert’s opinion and reliability was also checked by pilot study. Value of coefficient alpha was 0.711. Data was analyzed by using descriptive and inferential analysis techniques. It was concluded that students have specific preferences of learning media based on the educational setting, their grade levels and the task being undertaken.